2022
DOI: 10.1108/ejm-02-2021-0087
|View full text |Cite
|
Sign up to set email alerts
|

Incumbent defense strategies and new entrants market exit: the moderating role of relational market-based assets

Abstract: Purpose The purpose of this study is to empirically investigate the impact of incumbents’ defensive strategies, specifically price-cut and capacity expansion, on new entrants’ (NEs) exit decisions and examine the moderating role of incumbents’ relational market-based assets (RMBAs). Design/methodology/approach Drawing upon real options theory, an empirical study using logistic regression is conducted on a rich, multi-market data set of NE exits between 1997 and 2019 in the U.S. airline industry. Findings C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…The literature on market-based assets is fruitful, and recent studies have shown the benefits of incorporating two forms of market assets in business operations, such as customer loyalty (Li et al , 2019), firm performance (Rahman et al , 2022), marketing strategy effectiveness and efficiency (Varadarajan, 2020), innovation performance (Liu and Atuahene-Gima, 2018), profitability (Lin et al , 2020) and defense strategies (Aghaie et al , 2022). However, existing studies have not focused on the role of AI resources on market-based assets and have largely ignored the role of market-based assets on channel power.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The literature on market-based assets is fruitful, and recent studies have shown the benefits of incorporating two forms of market assets in business operations, such as customer loyalty (Li et al , 2019), firm performance (Rahman et al , 2022), marketing strategy effectiveness and efficiency (Varadarajan, 2020), innovation performance (Liu and Atuahene-Gima, 2018), profitability (Lin et al , 2020) and defense strategies (Aghaie et al , 2022). However, existing studies have not focused on the role of AI resources on market-based assets and have largely ignored the role of market-based assets on channel power.…”
Section: Theoretical Backgroundmentioning
confidence: 99%